Tłįcho˛ stories for Ekwò˛ management - Judas, Joseph (Rangifer, 2012)
This paper is adapted from contributions to the NACW Aboriginal Talking Circles, as well as the author’s contributions to two co-authored presentations: “Using dual knowledge systems to inform management decisions: a Wek’èezhìı Renewable Resources Board example,” with Jody Snortland; and “Monitoring Caribou and People,” with Allice Legat and John B. Zoe.